Effects of switching from a metered dose inhaler to a dry powder inhaler on climate emissions and asthma control: post-hoc analysis. Issue 12 (7th February 2022) - Woodcock, Ashley; Janson, Christer; Rees, Jamie; Frith, Lucy; Löfdahl, Magnus; Moore, Alison; Hedberg, Martin; Leather, David
Abstract : Objective: To compare the effects of switching from a pressurised metered dose inhaler (pMDI)-based to a dry powder inhaler (DPI)-based maintenance therapy versus continued usual care on greenhouse gas emissions (carbon dioxide equivalents, CO2 e) and asthma control. Methods: This post-hoc analysis was based on a subset of 2236 (53%) patients from the Salford Lung Study in Asthma who at baseline were using a pMDI-based controller therapy. During the study patients were randomised to fluticasone furoate/vilanterol (FF/VI) via the ELLIPTA DPI (switched from pMDI to DPI) (n=1081) or continued their usual care treatment (n=1155), and were managed in conditions close to everyday clinical practice. Annual CO2 e (kg) was calculated for the total number of maintenance and rescue inhalers prescribed. Asthma control was assessed by the proportion of ACT responders (composite of ACT total score ≥20 and/or increase from baseline ≥3). Results: The groups were well matched for demographic characteristics and baseline Asthma Control Test (ACT) total score (mean age: 49 years; mean ACT score: usual care, 16.6; FF/VI, 16.5). Annual CO2 e kg per patient (maintenance plus rescue therapy) was significantly lower with FF/VI DPI treatment ('switch' group) than usual care (least squares geometric mean 108 kg (95% CI 102 to 114) vs 240 kg (95% CI 229 to 252), p<0.001). Asthma control was consistently superior over the 12 months in the FF/VI DPI group compared with usual care. Conclusions: Patients switching from a pMDI-based to a DPI-based maintenance therapy more than halved their inhaler carbon footprint without loss of asthma control. The remaining inhaler carbon footprint could be reduced through switches from pMDI to DPI rescue medications or alternative lower-carbon footprint rescue inhalers if available. Asthma control improved in both groups, with greater control demonstrated in those initiated on FF/VI DPI. Trial registration number: NCT01706198 .